UJI TOKSISITAS KITOSAN CANGKANG KEPITING RAJUNGAN (Portunus pelagicus) DAN KEPITING BAKAU (Scylla serrata) DENGAN METODE BRINE SHIRMP LETHALITY TEST (BSLT) - Qisti Pristiwani; Ridwanto Ridwanto (Cross-border, 2023)
Rajungan and bakau are crab species that are very commonly found in Indonesia and are used as Indonesian fishery export commodities. However, unfortunately market demand only uses the meat, leaving a lot of shell waste for the environment. In fact, crab shells contain chemicals, including 30-40% protein, minerals (CaCO3), and 20-30% chitin. Chitin can be processed into chitosan which has many benefits for life. The purpose of this study was to determine the presence of chitosan in crab shells and to test its toxicity using the BSLT method. Chitosan is obtained from the isolation of chitin through the stages of deproteination, demineralization, depigmentation, and deacetylation of chitin into chitosan. The results of this study indicate that chitosan has not been isolated properly because the degree of deacetylation is only 48,7 % in crabs and 73,4% in mud crabs from a minimum standard of 75%. The degree of deacetylation was obtained from the results of the FT-IR test. Furthermore, the level of toxicity was seen with the results of the LC50 using the BSLT (Brine Shirmp Lethality Test) test. The results of probit analysis showed that the LC50 value was 3149.198 g/ml in rajungan crab chitosan and 3718.775 g/ml in bakau crab. So it can be concluded that chitosan from rajungan and bakau crab shells is not toxic and safe to use in life.